Smoking, depression, and suicide risk in the nursing staff of a Third-Level Hospital - Sánchez Núñez, Raquel Alejandra; Ramírez, C.; Gómez Meza, Marco Vinicio (UANL. Facultad de Medicina, 2014)
Objective: To determine the association between smoking, depression and suicide risk in the Nursing Staff of a University Hospital. Materials and method: this was a non-experimental, correlational cross-range study with observational analysis carried out between May 2012 and May 2013. We studied 232 nurses of the “Dr. José Eleuterio gonzález” University Hospital. two self-administered scales were applied, one for depression and one for suicide risk. Another hetero-applied scale of nicotine dependency was also used, and the subjects’ socio-demographic records were reviewed. Results: A total of 527,232 nurses were studied. A smoking prevalence of 22.8% (53 subjects), an operational depression prevalence of 15.1% (35 subjects), and a suicide risk of 5.1% (12 subjects) were found. Gender and age, speciically being male and young (mean age 29.2 years) were found to increase the risk of smoking. We also found that those nurses who had a partner and had a higher level of education smoked less compared to those who did not have a partner or had a lower degree of education. there were hospital departments where there was a higher prevalence of smoking, such as Internal Medicine and Shock trauma. No association between smoking and the presence of depression was found. Regarding depression, we found that those nurses who worked in the Department of Pensioners were more likely to develop operational depression than those working in any other department. We also found that the risk of presenting operational depression decreases as age increases. About suicide risk, a statistically signiicant association between smoking and suicide risk was found. We also found an association between operational depression and suicide risk.Conclusions: It is recommended to consider nicotine dependence as a fundamental part of psychopathology assessment because of its strong association with suicide risk. this study emphasizes the complexity of the issue of the comorbidity of smoking and psychopathology and the need to continue research lines.